2020
DOI: 10.7150/jca.36174
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin suppresses bladder cancer cell invasion and migration by regulating KDM3A and p21

Abstract: Emerging evidences have shown that Dihydroartemisinin (DHA), used in malaria treatment, possess anti-cancer activity. However, the study of its potential functional roles and the anti-cancer mechanisms in bladder cancer is limited. We performed this study to elucidate the influence of DHA in the biological behavior of bladder cancer cells and tried to explore the molecular mechanism. The results of CCK-8 assay showed that DHA significantly inhibited bladder cancer cell 5637, UMUC3 and T24 proliferation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Malignant tumors threaten the life safety of people all over the world and have become the main cause of death together with cardiovascular and cerebrovascular diseases and respiratory diseases (115). It has been demonstrated that DHA exerts significant anti-tumor activity in a variety of malignant tumors, and it has no toxicity to normal cells at appropriate doses (18,20,85,94,116,117). It has been found that DHA not only is used as an adjuvant drug in combination with other chemotherapy drugs to improve drug resistance and enhance tumor killing function, but also has a significant inhibitory effect on tumors (21,29,34,39,45,46,70).…”
Section: The Anti-tumor Activity Of Dhamentioning
confidence: 99%
“…Malignant tumors threaten the life safety of people all over the world and have become the main cause of death together with cardiovascular and cerebrovascular diseases and respiratory diseases (115). It has been demonstrated that DHA exerts significant anti-tumor activity in a variety of malignant tumors, and it has no toxicity to normal cells at appropriate doses (18,20,85,94,116,117). It has been found that DHA not only is used as an adjuvant drug in combination with other chemotherapy drugs to improve drug resistance and enhance tumor killing function, but also has a significant inhibitory effect on tumors (21,29,34,39,45,46,70).…”
Section: The Anti-tumor Activity Of Dhamentioning
confidence: 99%
“…6 Lysine demethylase 3A (KDM3A), also termed Jumonji domain-containing 1A (JMJD1A) and Jumonji C (domain-containing histone demethylase 2A) JHDM2A, is a histone H3 lysine 9 (H3K9) dimethyl and monomethyl (me2/1) demethylase has been implicated in many cellular processes from proliferation to progression, and is reported as an advanced target for cancer treatment. 7,8 But the role of KDM3A in CC development remains less concerned. Interestingly, a previous report suggested that KDM3A could interactwith the ETS proto-oncogene transcription factor 1 (ETS1) flanking its start site through a H3K9me2 demethylation manner, which leads to the further metastasis of Ewing sarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some arts are more toxic while others are more protective. For example, artemisinin and artemether are more protective while dihydroartemisinin and artesunate are more toxic and used more often in anti-cancer studies [ 87 , 88 ]. Finally, the effect of arts may be different in different cell types.…”
Section: Discussionmentioning
confidence: 99%